’Andhi’, the convective duststorm of northwest India - JOSEPH, P. V.; RAIPAL, D. K.; DEKA, S. N. (MAUSAM, 1980)
The convective duststorm occurring over Northwest India during the pre-monsoon season is called ’India’. In this paper a study is made on Andhi of Delhi using available meteorological records of recent years. From records of horizontal visibility and surface wind speed variations associated with them, Andhi has been classified into 4 types. Radar PPI photographs studied shows that the distance between the cumulonimbus cloud or squall line as seen in the radar and the ground level position of the duststorm (or gust-front) can be as large as 30 kilometres. The paper also gives a review of the existing knowledge on the phenomenon of convective duststorm (Andhi and Haboob).